EFEKTIVITAS METODE LATIHAN SENSORIS MOTOR DALAM MENINGKATKAN KEMAMPUAN MENULIS HURUF (VOKAL) BAGI ANAK TUNARUNGU SEDANG - Defni - Darwis (Jurnal Penelitian Pendidikan Khusus, 2014)
The background of this research is, there is a child who can not write letters, especially vowels in SDLB N 015 Bangkianang, Riau. Sensory motor training method is a method using flexibility exercises fine motor, resulting in precise coordination between the eye and the hand, the purpose of this study is to prove the effectiveness of sensory motor in improving the writing skills of deaf children were in SDLB N 015 Bangkinang, Riau. This type of research is a single research subject with ABA desaign. The results of this research is effective method of motor sensory exercises to improve writing skills for children with hearing impairment vowels were in SDLB N 015 Bangkinang, Riau.